KORELASI TERHADAP PERSEPSI PENGGUNAAN MEDIA ONLINE DIGITAL INTERAKTIF DENGAN KEMAMPUAN MENULIS BAHASA INGGRIS SISWA TINGKAT SMA - Nisa, Khairun; Nurweni, Ari; Yufrizal, Hery; Mahful, Mahful (Universitas Lampung, 2024)
The use of interactive digital online media in the English teaching and learning process has become increasingly widespread, especially since the outbreak of the Covid-19 outbreak in 2020. In this case, not only educational-based media such as Google Classroom, Edmodo, or various digital dictionaries, but also video conference service provider software, to social media and entertainment site networks have transformed into unlimited sources of teaching materials, especially for the field of English language science. Students are one of the groups that actively utilize various types of media as a means of learning and gaining knowledge and techniques that can be applied in their English production. This study was designed to identify high school students related to the use of internet-based interactive digital media and relate it to their English writing skills. A survey using a closed-ended questionnaire was conducted to obtain responses that lead to students' use of digital online media to then be analyzed in relation to their achievements in the writing test. This study found that the correlation between the use of interactive online media and students' English writing skills has a negative relationship. This can be seen from students' English writing skills which are inversely proportional to students' perceptions of the use of interactive online media.Penggunaan media online digital interaktif dalam proses belajar mengajar Bahasa Inggris semakin marak terutama sejak merebaknya wabah Covid-19 pada 2020 lalu. Dalam hal ini, tak hanya media berbasis edukasi seperti Google Classroom, Edmodo, atau pun beragam kamus digital, namun juga perangkat lunak penyedia layanan video conference, hingga media sosial dan jejaring situs hiburan bertransformasi menjadi sumber bahan ajar tak terbatas terutama untuk bidang keilmuan Bahasa Inggris. Pelajar menjadi salah satu kelompok yang secara aktif memanfaatkan ragam jenis media ini sebagai sarana belajar dan memperoleh pengetahuan serta teknik yang dapat diterapkan dalam produksi Bahasa Inggris mereka. Penelitian ini dirancang untuk mengidentifikasi pelajar di tingkat SMA terkait penggunaan media digital interaktif berbasis internet dan menghubungkannya dengan keterampilan mereka dalam menulis bahasa Inggris (writing). Survei dengan menggunakan close-ended questionnaire dilakukan untuk memperoleh respon yang mengarah pada penggunaan media online digital para pelajar untuk kemudian dianalisis kaitannya dengan capaian mereka dalam writing test. Dalam penelitian ini didapati bahwa korelasi antara penggunaan media online interaktif dengan kemampuan menulis Bahasa Inggris siswa memiliki hubungan yang neagtif. Hal ini terlihat dari kemampuan menulis Bahasa Inggris siswa berbanding terbalik dengan persepsi siswa terhadap penggunaan media online interaktif.